Evaluating the Effects of Polymers on Microbially Induced Carbonate Precipitation - Yan, Z.; Gowthaman, S.; Nakashima, K.; Kawasaki, S. (11th International Conference on Geotechnique, Construction Materials and Environment, GEOMATE International Society, 2021)
Microbially induced carbonate precipitation (MICP) is relatively a new environmentally friendly soil improvement method. In MICP process, the formation of calcium carbonate occurs within the soil matrix as the consequence of biochemical process mediated by ureolytic bacteria. The objective of this preliminary work is to evaluate the effects of adding polymers on MICP process. Basically, the polymers are organic macromolecules and have potential to offer several benefits such as increasing solution viscosity, extending supply time, localization of cementation reactions, reduction of harmful byproduct ammonium and enhancement of strength. For the above-mentioned objective, two different types of polymers are studied: (i) Polyvinyl alcohol (PVA) and (ii) Polyacrylic acid (PAA). Lysinibacillus xylanilyticus are cultivated in the standard medium with varying contents of polymers. The growth and urease activity of the bacteria are determined with the incubation time. In addition, set of test tube tests is performed to assess the precipitation characteristics of calcium carbonate at the presence of polymers. The outcomes indicated that the polymers do not have any adverse effects on the growth of bacteria. However, the PAA is found significantly enhance the urease activity compared with typical bacteria culture medium, whereas it is not evidenced in PVA. Moreover, compared to the typical MICP process, the addition of polymers produce more spherical-shaped calcium carbonate crystals, which highly differ from typical rhombohedral-shaped crystals. With the above findings, future works are recommended on soil to investigate the cementation efficiency and adsorption of ammonium by-products
Keywords: Microbially induced carbonate precipitation (MICP); soil improvement; polymer; urease activity; crystal morphology